A study on sustainability and ESG in the service sector in India: Benefits, challenges, and future implications - Leonidas Efthymiou; Ambika Kulshrestha; Sandeep Kulshrestha (Administrative Sciences, 2023)
At the intersection of digitization and sustainability, the current article explores the application of environmental, social, and corporate governance (ESG) in the service sector in India. The analysis draws on findings collected through questionnaires and interviews (mixed methods) with managers at middle, senior, and top levels of the hierarchy. The findings suggest that technology can both facilitate and hinder the sustainability effort; therefore, the implications on internal stakeholders, such as workers and managers, can be both positive and negative. Additionally, technologies that are taken for granted in certain parts of the world may be inappropriate in the Indian context. As a result, sustainability frameworks are implemented selectively rather than holistically. The adoption of an ESG framework has a largely positive impact on investors. While companies do not place much emphasis on employees' wellbeing and 'human rights', they still link ESG to 'Supply Chain Sustainability'. Contributing to the signaling theory, there is also evidence of firms' motivation to adopt ESG practices for the purposes of legitimacy and forming external stakeholders' perceptions. The current study is both timely and important due to the high interest in the application of tools facilitating sustainability performance. The study contributes to both the literature and practice, since it adds to our understanding concerning the challenges faced by firms in implementing ESG practices, whereas it also enables administrators to identify areas for the further development of sustainable practices.
Keywords: 350; corporate social responsibility; environmental social and corporate governance (ESG); green technological innovation; service sector; socially responsible investment (SRI); sustainability; sustainable development goals (SDGs)